Super sde kicks - Than, Gavin Aung (North Sydney, NSW Puffin Books, 2019)
The Mother of the Seas is sick of humans using the oceans as a junkyard, so she decides to give the land dwellers a taste of their own medicine. Prepare for an unbelievable underwater menace that threatens to destroy the entire world!
3-5
Keywords: Language